IMITATION OF THE NATURAL LANDSCAPE FOR CREATING THE PHYTOENVIRONMENT OF INNOVATIVE BUILDINGS - Votinov, М.; Smirnova, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article is devoted to the study of the peculiarities of the formation of innovative buildings imitating the natural landscape when creating their phytoenvironment. It has been established that the phytoenvironment is a closed or semi-closed architectural and landscape space with clear boundaries. It is one of the elements that ensures the connection of the interior spaces of innovative buildings with nature. It was determined that the volume-planning solution of innovative buildings with a phytoenvironment should include the formation of main and additional rooms with the possibility of organizing various relaxation processes. This is facilitated by the phytoenvironment formed in the building. The main characteristic features of the formation of the internal space of innovative buildings with the inclusion of a natural component have been established. It was determined that the formation of a phytoenvironment with imitation of a natural landscape in the structure of innovative buildings should be carried out using a regular, landscape and mixed planning structure and using various means of landscape design. The specifics and methods of phytoenvironment formation with imitation of different types of natural landscape in the structure of innovative buildings were studied. The main ones are the formation of a multi-zonal architectural and landscape space with high ecological indicators; integration of the natural environment into an architectural object to create unique landscape compositions with sound accompaniment and additional visual effects; creation of high-quality microclimatic characteristics in the interior environment of the object (complex inclusion and combination of all types of natural elements); individual light-colored solution of landscape compositions of the phytoenvironment in the structure of innovative buildings. It was determined that the search for a harmonious image of the phytoenvironment during its formation should be combined with careful consideration of the type of natural landscape – forest, steppe, riverside, mountain, etc. It was determined that the creation of a unique phytoenvironment is achieved through the use of individual design – a project that not only creates a certain image of imitation of the natural landscape, but also contributes to a comfortable stay in it. As a result of the research, promising trends in the formation of a phytoenvironment with imitation of a natural landscape in the structure of innovative buildings were determined. They are aimed at the creation and development of a multifaceted space of the phytoenvironment with the help of compositional association, which involves the systematic formation in the volume-planning structure of innovative buildings of individuality, functional and aesthetic comfort.